RELIGIOUS MODERATION STUDIES: EVALUATION OF RESPONSIVENESS TO IT’S IMPLEMENTATION IN THE EDUCATIONAL PROCESS - I Wayan Agus Gunada; I Wayan Widiana; I Nyoman Jampel; I Gede Ratnaya (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This study aims to explain the responsive evaluation of the implementation of religious moderation education. Religious moderation is a principle of life in multicultural life, promoting tolerance attitudes and behaviors, but in some events, acts of intolerance still occur and become a cause of conflict. So it is crucial to examine the position of education in implementing these principles. The study was conducted with a responsive evaluation approach through a literature analysis of research results on religious moderation education. Based on the analysis results, religious moderation is implemented to form moderate attitudes of religious people to build tolerance and harmony. As a process, education becomes a medium of value transformation for students so that it can strengthen religious moderation in society. A strengthening strategy is needed in its implementation because implementing these principles in society still needs to be improved. This study can become relevant literature for related studies and strengthen insights into implementing religious moderation.